Harp Seals: Monitors of Change in Differing Ecosystems - Stenson, Garry B.; Haug, Tore; Hammill, Mike O. (Frontiers in Marine Science, 2020)
Harp seals are the most abundant marine mammal in the north Atlantic. As an ice obligatory predator, they reflect changes in their environment, particularly during a period of climatic change. As the focus of a commercial hunt, a large historic data set exists that can be used to quantify changes. There are three populations of harp seals: White Sea/Barents Sea, Greenland Sea and Northwest Atlantic. Although important historically, recent catches have been low in the two northeast Atlantic populations and do not appear to be influencing trends in either population. Massive mortalities of White Sea/Barents Sea seals occurred during the mid 1980s due to collapses in their major prey. Between 2004 and 2006, pup production declined by 2/3 and has remained low. Body condition declined during the same period, suggesting that ecosystem changes may have resulted in reduced reproductive rates, possibly due to competition with Atlantic cod. The most recent estimate pf pup production in the Greenland Sea also suggests a possible decline during a period of reduced hunting although the trend in this population is unclear. Pupping concentrations are closer to the Greenland coast due to the reduction in ice in the traditional area and increased drift may result in young being displaced from their traditional feeding grounds leading to increased mortality. Reduced ice extent and thickness has resulted in major mortality of young in the Northwest Atlantic population in some years. After a period of increase, the population remained relatively stable between 1996 and 2013 due to increased hunting, multiple years with increased ice-related mortality of young seals, and lower reproductive rates. With a reduction in harvest and improved survival of young, the population appears to be increasing although extremely large interannual variations in body condition and fecundity have been observed which were found to be influenced by variations in capelin biomass and ice conditions. Each of these populations has been impacted differently by changes in their ecosystems and hunting practices. By identifying the factors influencing these three populations, we can gain a better understanding of how species may respond to changes that are occurring in their ecosystems.